The Dynamic Temperate and Boreal Fire and Forest-Ecosystem Simulator (DYNAFFOREST): Development and evaluation. (October 2022) - Hansen, Winslow D.; Krawchuk, Meg A.; Trugman, Anna T.; Williams, A. Park
Abstract: Fire is a dominant disturbance in temperate and boreal biomes, and increasing burned area with climate change may fundamentally alter forests. Improved information about how fire-induced changes to forests may feedback to affect subsequent burning at regional scales could inform forest management and climate-mitigation strategies. However, fire is simplistically represented in Earth System Models, and regional statistical fire models often assume sufficient fuels, contributing to uncertainty in future projections. To address this challenge, we developed the Dynamic Temperate and Boreal Fire and Forest-Ecosystem Simulator (DYNAFFOREST). DYNAFFOREST represents the hierarchical structuring of forests, from individual cohorts to continental extents, making it possible to simulate feedbacks between fire and forests at broad scales over decades to centuries. We parameterized DYNAFFOREST for the western United States of America and benchmarked simulations with observations. DYNAFFOREST recreated patterns of forest cover, structure, and downed fuels, and was capable of capturing average 20th-century fire activity. Highlights: Feedbacks between fires and forest are not well captured in broad-scale models. DYNAFFOREST simulates temperate and boreal fire and forests as a coupled system. The model captures forest and fire characteristics in the western United States of America. DYNAFFOREST is a powerful framework for diagnosing the causes and consequences of increasing fire.